Keefektifan Model Jigsaw Dan STAD Terhadap Pencapaian Karakter Dan Kemampuan Numerasi Siswa Kelas V SD - Kustantina (Universitas Ngudi Waluyo, 2023)
In the learning process in class V SDN Karanggeneng 02, the students' character achievement and students' numeracy skills were still low. This condition was improved through the use of innovative learning models. The researcher aimed to determine the effectiveness of the Jigsaw and STAD learning models on the character and numeracy achievement of fifth grade students. This research is an experimental research with a learning observation research design and pretest posttest. The samples in this study were the VA class using the Jigsaw learning model and the VB class using the STAD learning model. The data obtained from the results of the research were analyzed using a statistical test, then the t-test results were carried out. From the results of the analysis and tests, this study showed a significant difference in effectiveness. In the Jigsaw model, the level of effectiveness is 77.02%, while in the STAD model it is 48.32%. So that it can be stated that the Jigsaw learning model is more effective in achieving the character and numeracy abilities of fifth grade elementary school students. Dalam proses pembelajaran di kelas V SDN Karanggeneng 02 pencapaian karakter siswa dan kemampuan numerasi siswa masih rendah.Kondisi tersebut diperbaiki melalui penggunaan model pembelajaran yang inovatif.Peneliti bertujuan mengetahui keefektifan model pembelajaran Jigsaw dan STAD terhadap pencapaian karakter dan numerasi siswa kelas V . Penelitian ini merupakan penelitian eksperimen dengan desain penelitian observasi pembelajaran dan pretes posttes.Sempel dalam penelitian ini adalah kelas VA menggunakan model pembelajaran Jigsaw dan kelas VB menggunakan model pembelajaran STAD. Perolehan data dari hasil penelitian dianalisis menggunakan Uji statistic,selanjutnya dilakukan Uji-t hasil. Dari hasil analisis dan uji tersebut penelitian ini menunjukkan tingkat perbedaan keefektifan yang signifikan. Pada model Jigsaw tingkat keefektifannya 77,02% sedangkan model STAD 48,32%. Sehingga dapat dinyatakan model pembelajaran Jigsaw lebih efektif terhadap pencapaian karakter dan kemampuan numerasi siswa kelas V SD.